PENGARUH KETERLIBATAN PEMAKAI DAN KEMAMPUAN TEKNIK PERSONAL TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI PADA KANTOR SAMSAT DELI SERDANG - Ifan Fadillah Harahap; Alistraja Dison Silalahi (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2023)
This study aims to determine the effect of user involvement and personal technical skills on the performance of accounting information systems at the Deli Serdang Samsat Office. This research is a type of quantitative research. The sampling technique was carried out using a non-purposive sampling technique. In research, respondents are people who are asked to provide information about a fact or opinion. This information can be conveyed in writing, namely when filling out a questionnaire, or verbally, when answering an interview. Respondents in this study were all employees who worked at the Deli Serdang Samsat Office, totaling 30 respondents. The data analysis technique used in this study is multiple linear regression analysis with SPSS 22 software tools. The multiple linear regression equation, namely Y = 42.262 + 0.047X1 + 0.062X2 + e illustrates that the independent variable (independent) is user involvement (X1), and Personal Technical Ability (X2) in the regression model can be stated if one independent variable changes by 1 (one) and the other is constant, then the change in the dependent variable (Y) is equal to the coefficient value (b) of the variable value of 42.262 giving the understanding that if User Engagement (X1) and Personal Technical Ability (X2) simultaneously or together do not change or are equal to zero (0), then the value of the Company (Y) is 42.262 units.